Flood Inundation Modelling and Reduction by Dike Construction in Urban Areas: A Case Study in Erbil, Iraqi Kurdistan - Anwer Hazim Dawood; Dana Khider Mawlood (Journal of Studies in Science and Engineering)
In recent years, Erbil has faced an elevated risk of floods due to climate change and incorrect land development design and management. To tackle this issue, this study uses Hydrologic Engineering Center River Analysis System (HEC-RAS) software to address flood inundation and reduction by constructing dikes. This involved using a digital elevation model (DEM) in the study area (Mass Village) east of Erbil. The study delineated the catchment area and employed watershed modelling system (WMS) software. Furthermore, Hydrologic Engineering Center Hydrologic Modeling System (HEC-HMS) software was used to create a flood hydrograph, which the HEC-RAS software used to estimate flood inundation areas, velocity, and water levels. The study identified water surface areas and velocities prone to flooding in the urbanised area, with water depths ranging from 0 to 5 m. The model was rerun after the construction of the dikes, resulting in water depths ranging from 0 to 7.2 m upstream of the dikes. The modelling results indicated a water depth of 0 m downstream of the dike (protected area), demonstrating that the dike's construction successfully reduced flooding in the urbanised area.